THÊMIS: um sistema para análise forense de DNA utilizando Redes Baysianas - Costa, José Tenório César (2009)
Since the mid 80, DNA fingerprinting has revolutionized forensic science, providing a powerful tool for research, currently being widely used in studies of paternity. Laboratories that work with forensic analysis of DNA carry increasing amounts of such studies and encourage the use of software systems that help with this type of analysis. One of the requirements for software of this magnitude is reliability, considering the level of detail of the study. Thus, it is interesting the use of formal methods. In this work, a software system called THÊMIS is built. THÊMIS uses Bayesian Networks as knowledge representation about studies of paternity, using inferences to obtain the results required by the forensic genetics regarding the calculation of the Index of Paternity (IP)